Fostering authentic inquiry at multiple levels through participatory action research (Pedagogical Horizons, 2021)
Participatory action research processes (PAR)  have proven to be effective with regard to advancement in education. This paper explores how an inquiry-oriented teaching approach can be realised in secondary school in a participatory process involving three levels, namely pupils, teachers, and a supporting team of researchers. The intention of the developmental project is to unfold certain criteria typical of participatory inquiry-learning arrangements on all these levels. The aim of the study is to understand the parameters conducive to the evolvement of the criteria of inquiry learning and the specific methods teachers use in their lessons. This is achieved by quantitative analysis of data gathered by the practitioners and qualitative analysis of guided interviews of the supporting research team with eight teachers. It turns out that sound knowledge of the theory, support from researchers, participation in the learning experience of a group, and, most importantly, teachers’ trust in the capabilities of the learners are crucial to the effective use of the participatory approach to inquiry in classrooms. It can be concluded that, reflection and analysis of actions in class will eventually result in new cycles of inquiry learning, thus fuelling the participatory action research cycle and the school developmental process.
Keywords: bottom-up school developmental processes; inquiry learning; participatory action research